LITERASI MEDIA BERBASIS KEARIFAN LOKAL MASYARAKAT BALI - Darmastuti, Rini; Purnomo, Jusuf Tjahjo; Utami, Birmanti Setia; Yulia, Hanita (Jurnal Studi Komunikasi, 2019)
This research aims to describe the Balinese local wisdom as the groundwork for media literacy and to build media literacy model. The observations and in-depth interviews to Balinese prominent leaders were conducted in his qualitative research. The results show that (1) Nawangleh and Tri Hita Karana are the Balinese local wisdom; (2) The principle of Nawangleh and Tri Hita Karana becomes the basis for filtering, sorting, and choosing the messages shown on the television; (3) The opinion leaders that convey the messages of media literacy are Kelian Adat and Sanggar’s mentors (housewives), karang taruna’s leaders (teenagers), and school teachers (children).